The diagnosis of trophoblastic tumours from uterine curettings - Elston, C. W. (1972)
The reliability of the diagnosis of choriocarcinoma from uterine curettings is still a matter for debate, and few pathologists see enough material for an objective clinico-pathological study. In the present survey curettings from 54 patients were examined, 38 during follow up of a hydatidiform mole, 12 following a normal pregnancy and four after a spontaneous abortion. Four histological categories were identified: villous, simple trophoblast, trophoblast with appearances suspicious of choriocarcinoma, and trophoblast diagnostic of choriocarcinoma. The presence of hydropic villi is evidence that malignant change has not developed at that time and only two of the 20 patients in this group subsequently developed choriocarcinoma. The interpretation of simple or suspicious trophoblast depends on the antecedent gestation: if it were molar, malignant change is relatively infrequent (choriocarcinoma subsequently developed in four out of 15 patients); if it were non-molar then malignancy is a strong possibility (choriocarcinoma developed in nine and metastatic trophoblastic disease in four of the 13 patients). The correct management of the individual patient can only be achieved by a full consideration of the histological features together with the clinical history and findings.